Discovering effective pedagogical and evaluation approaches for learning objects in medical education - Calbraith, Davina (2011)
In 2004 unexplained pedagogical barriers were limiting Learning Object (LO) development. Few reference points existed preventing the formation of specific pedagogical questions as to the nature of these barriers - hence this PhD's rationale. This thesis 'uncovers' the most effective pedagogical and evaluation/assessment* approaches for LO design in Medical Education, and the underlying principles within these approaches - i.e. what is effective, and why.